The Views of Pre-service EFL Teachers on Teaching Assistant Practice in Language Teaching - BATAKLAR, SİNAN; Bahadır, Aygül (İstanbul Kültür Üniversitesi, 2024)
The purpose of the study is to analyze the views on Teaching Assistant Practice (TAP) gathered from five senior English Language Teaching (ELT) students. The primary aim is to investigate and reveal how TAP affects EFL pre-service teachers’ teaching quality. The study was designed using a qualitative approach and a purposive sampling approach. The data was collected using open-ended questions and was analyzed using the qualitative content analysis approach. Based on the evidence, significant themes regarding the TAP were discovered. The following were the themes: excelling on pedagogical content knowledge and teaching quality, raising awareness, and improving teacher roles, the benefits of being professionally present as a teacher in the classroom, and the enhancement of multitasking. It was concluded that with the responses obtained from the prospective teachers, the themes mentioned create a positive atmosphere for them to sharpen their practical teaching skills in a professional sense.
İngilizce Öğretmeni Adaylarının Dil Öğretiminde Asistanlık Uygulamasına İlişkin Görüşleri
Keywords: Teaching Assistance; Teaching Assistance Practice; Teaching Quality; Teaching Assistantship in EFL Practices; EFL Teacher Education